The effectiveness and safety of integrative medicine for chronic heart failure: An umbrella review - Wei J. Chua; Jing Liu; Kaitlyn Lam; Alison Maunder; Chhiti Pandey; Adele E. Cave; Allana O’Fee; Guoyan Yang; Aya Mousa; Carolyn Ee (Complementary Therapies in Medicine)
Background and purpose: Heart failure (HF) is associated with multi-organ dysfunction and significant morbidity and mortality. Despite advances in treatment, prognosis remains poor, highlighting the need to explore adjunctive therapies such as integrative medicine. This umbrella review synthesises top-tier evidence from systematic reviews and meta-analyses of randomised controlled trials (RCTs) assessing the safety and effectiveness of integrative medicine in patients with HF, in order to inform clinical decision-making. Methods: We searched MEDLINE, Cochrane, PsycINFO and EMBASE until April 2024. Primary outcomes included mortality, hospitalisation rates, and severity or prognostic indicators, including brain natriuretic peptide (BNP) and exercise capacity. A hierarchical evidence synthesis method was used whereby we included the most recent, highly ranked and comprehensive reviews for our research question. We assessed review quality using ‘A MeaSurement Tool to Assess systematic Reviews’ and, where possible, evidence certainty for our primary outcomes using the Grading of Recommendations Assessment, Development and Evaluation approach. Results: Twenty-two reviews were included. Co-enzyme Q10 or Tai Chi may reduce mortality and hospitalisation rates (moderate certainty evidence), and acupuncture or intravenous Chinese herbal medicines may improve BNP (low to very low certainty evidence). The benefits of yoga and other nutrient supplements including L-carnitine remain unclear. Vitamin E may increase hospitalisation rates and should be avoided. Conclusion: The evidence for most integrative medicine modalities for adjunctive management of HF remains limited. Well-designed and rigorous RCTs are needed, particularly with long-term follow up and evaluation of clinically meaningful outcomes.